Southside With You - Calloway, Vanessa Bell; Scola, Pat; Schiff, Evan; Taylor, Stephen James; 1957; Teitel, Robert; Sumpter, Tika; Tanne, Richard; Sawyers, Parker; Lions Gate Entertainment (Firm); Get Lifted Film Co.; Fermion Films; et al. (Santa Monica, California, 2016)
Chronicles the summer afternoon in 1989 when the future President of the United States, Barack Obama, wooed the future First Lady, Michelle Robinson, on an epic first date across Chicagos South Side.
Keywords: Drama; 1964-; Obama, Barack; Drama; Obama, Michelle; Fiction films; Video recordings for the hearing impaired; Biographical films; Romance films; Feature films